IAS Versus U.S. GAAP: Information Asymmetry–Based Evidence from Germany's New Market - LEUZ, CHRISTIAN (Journal of Accounting Research, 2003)
abstract Motivated by the debate about globally uniform accounting standards, this study investigates whether firms using U.S. generally accepted accounting principles (GAAP) vis‐à‐vis international accounting standards (IAS) exhibit differences in several proxies for information asymmetry. It exploits a unique setting in which the two sets of standards are put on a level playing field. Firms trading in Germany's New Market must choose between IAS and U.S. GAAP for financial reporting, but face the same regulatory environment otherwise. Thus, institutional factors such as listing requirements, market microstructure, and standards enforcement are held constant. In this setting, differences in the bid‐ask spread and share turnover between IAS and U.S. GAAP firms are statistically insignificant and economically small. Subsequent analyses of analysts' forecast dispersion, initial public offering underpricing, and firms' standard choices corroborate these findings. Thus, at least for New Market firms, the choice between IAS and U.S. GAAP appears to be of little consequence for information asymmetry and market liquidity. These findings do not support widespread claims that U.S. GAAP produce financial statements of higher informational quality than IAS.